Radio comunitaria digital, una vía para la visibilización del cantón Quinsaloma, Provincia de Los Ríos - Zapata Briones, Karla Elizabeth (2020)
The following case study deals with communication in the social community context, the use of digital media as o communication tool when interacting with listeners or listeners. Knowing the various potentials offered by radio are many, which will allow young and old alike to emerge and develop in a big world, to know its scope, in addition, to forge their potential and take it to the top. In a community radio station, you not only fulfill the activity of communicating, on the contrary, you are solving the problems that the cause in society, finding a point of balance between the people and their leaders, being that voice of struggle and progress that will make possible the change of all. For example: in agriculture, in art, in sport, in tourism or in gastronomy. All this can be demonstrated through communication and information, together with digital, each of the diversities that exist within the community are made known.